Upaya Meningkatkan Kemampuan Motorik Kasar Melalui Permainan Tradisional Perepet Jengkol Pada Anak Usia Dini 4-5 Tahun di Tk Al Falah - Neti Wiharti (PT. Alahyan Publisher Sukabumi, 2025)
This research aims to improve the gross motor skills of children aged 4–5 years through the traditional game of Perepet Jengkol at Al Falah Kindergarten. Traditional games are chosen because they have elements of movement that are able to stimulate children's physical development, especially in terms of balance, coordination, and muscle strength. This research uses the Classroom Action Research (PTK) method which is carried out in two cycles, each of which consists of the stages of planning, implementation, observation, and reflection. The subjects in this study were 15 children of group A aged 4–5 years. Data collection techniques are carried out through observation, documentation, and field notes. The gross motor indicators observed included the ability to jump, maintain balance, and coordinate movements when participating in the Perepet Jengkol game. The results of the study show that the game of Perepet Jengkol can improve children's gross motor skills. At the pre-action stage, only 51.25% of children met the developmental criteria according to age. After the action in cycle I, it increased to 70.41% and in cycle II it reached 87.08%. This game has proven to be effective because it is able to provide fun learning, actively move the body, and increase children's courage and independence.